Epidemiological aspects of breast cancer in C.A.S.M.U. - Musé, Ignacio; Piazza, Nelly; Ottati, Alfio; Sabini, Graciela (Cirugía del Uruguay, 1989)
Authors made a revlsion of all C.A.S.M.U. anatomopathological reports between 1983 and 1985, covering 2.612 cases of tumoral pathology, which represent an average of 871 new annual patients with hystoiogical diagnosis. Breast cancer is in the second place in incidence (12,7%) on the total tumour population (both sexes), preceded by skin tumours (16,2%) and followed by colorrectal cancer (11,1%) and lung cancer.